Mapeamento da participação feminina em ações de ensino, pesquisa e extensão no Instituto Federal de São Paulo (IFSP): um estudo exploratório - Santos, Camila Fátima dos (2019)
The present study has the purpose of studying the mapping of female participation in teaching, research and extension actions within the scope of the Federal Institute of Education, Science and Technology of São Paulo (IFSP), and the first of these three pillars is analyzed gender issues in a more comprehensive way. To justify the relevance of the work, it is based on the idea that science is not neutral and that, therefore, there are significant differences in the participation, rise and permanence of women in science and technology. Thus, the results obtained provide a diagnosis of how the female participation has been worked in the institution, making possible the adoption of strategic decisions in order to promote gender equity in its context. The research is structured in three parts, (i) bibliographical survey, (ii) documentary research and (iii) field research. The first one allows us to construct an overview of the subject in the areas of science and technology in a national and international panorama, as well as a historical trajectory of the feminine achievements in the promotion of equity and the definition of concepts pertinent to the theme. The second phase, documentary research, analyzes programs, projects and actions focused on gender, or more specifically on women's participation, in the three pillars that support the institution: teaching, research and extension. In the field of education, the pedagogical projects of the 138 undergraduate courses offered in the IFSP by the year 2018 were examined, identifying disciplines that address the issue of gender in its menu or bibliography. In the scope of the extension, programs, projects and other actions were mapped through open data of the IFSP, having as object of analysis the female participation. Concluding the documentary research, we present data related to research groups linked to the institution, also mapping the presence of women in certain contexts. Finally, some of the proponents of these actions, obtained through interviews, are brought in order to better characterize the context and final considerations regarding the research as a whole. It is concluded that there are significant advances on the part of the Institution in promoting a more egalitarian environment, since the discussion has been gaining strength in the various spheres. However, there are still gaps in studies and initiatives to be taken, since there are areas with a very small female participation when compared to men.